2016
DOI: 10.1038/srep32853
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of regular and on-demand regimen of PED5-Is in the treatment of ED after nerve-sparing radical prostatectomy for Prostate Cancer

Abstract: Phosphodiesterase type-5 inhibitors (PDE5-Is) have been recommended as first line therapy for erectile dysfunction for patients received nerve-sparing radical prostatectomy for prostate cancer. We examed the efficiency of PDE5-Is and considered the optimal application. Systematic search of PubMed, Embase and the Cochrane Library was performed to identify all the studies. We identified 103 studies including 3175 patients, of which 14 were recruited for systematic review. Compared with placebo, PDE5-Is significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The superiority of on‐demand treatment modality in improving a less stringent outcome, such as the IIEF score, has been already demonstrated in a previous systematic review (Wang et al ., ). Surprisingly, another recent systematic review (Qiu et al ., ) reached opposite results, showing the superiority of regular regimens of treatment. Although the authors adduced some arguments to explain this pattern of results, some doubts on the accuracy of analysis of single trials cast uncertainties on the quality of conclusions drawn.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The superiority of on‐demand treatment modality in improving a less stringent outcome, such as the IIEF score, has been already demonstrated in a previous systematic review (Wang et al ., ). Surprisingly, another recent systematic review (Qiu et al ., ) reached opposite results, showing the superiority of regular regimens of treatment. Although the authors adduced some arguments to explain this pattern of results, some doubts on the accuracy of analysis of single trials cast uncertainties on the quality of conclusions drawn.…”
Section: Discussionmentioning
confidence: 96%
“…7 of Qiu's et al . () systematic review. In fact, in the original trial, Pavlovich concluded that there was a similar efficacy of both nightly and on‐demand treatment modality on recovery of EF, as assessed by absolute IIEF‐EF scores (Pavlovich et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…67 68 The effect seems to be ameliorated with a regular treatment regime compared with on-demand use of PDE-5-I in patients with ED after radical prostatectomy. 69 The current limited evidence demonstrates, that daily oral intake of PDE-5-I seems to have also a relevant positive effect on ED in 55%-88% of patients after PRF with or without associated PFUI. [70][71][72][73] Furthermore, the efficacy of pharmacological therapy can also be supported with mechanical aids, such as the use of vacuum erection devices or low-intensity shock-wave therapy.…”
Section: Rate Of Ed After Prfmentioning
confidence: 99%
“…Tadalafil inhibits the formation of cyclic guanosine monophosphate and prolongs nitric oxide (NO), thereby increasing NO availability in the endothelial area (Lasker et al, 2013). Previous studies have compared different doses of tadalafil, that is, 5 mg daily versus 20 mg when required, and have reported favourable results for either dosage (Burns et al, 2015; Hatzichristou et al, 2015; Qiu et al, 2016). DM leads to long‐term microvascular complications, causing severe ED (Aslan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have compared different doses of tadalafil, that is, 5 mg daily versus 20 mg when required, and have reported favourable results for either dosage (Burns et al, 2015;Hatzichristou et al, 2015;Qiu et al, 2016). DM leads to long-term microvascular complications, causing severe ED (Aslan et al, 2009).…”
mentioning
confidence: 99%